Polydrug use among kratom users: Findings from the 2011 Thailand National Household Survey. (4th July 2018) - Likhitsathian, Surinporn; Jiraporncharoen, Wichuda; Aramrattana, Apinun; Angkurawaranon, Chaisiri; Srisurapanont, Manit; Thaikla, Kanitta; Assanangkornchai, Sawitri; Kanato, Manop; Perngparn, Usaneya; Jarubenja, Ratana
ABSTRACT: Despite the availability of numerous anecdotal reports of polydrug use in kratom users, few studies have been carried out in Thailand. This study aimed to explore the problem of polydrug use among Thai kratom users. A national household survey on the prevalence of substance use was conducted in 2011 using a multistage random sampling technique. Participants were interviewed using a structured questionnaire. The frequency of other substance use was compared between respondents with and without a history of kratom use. Of the total sample (18, 457), 544 (2.9%) acknowledged kratom use. Eighty-nine (46.1%) used it almost every day. The mean age of users (SD) was 42.7 (12.8) years old, 459 (84.4%) were male, and 264 (48.5%) had used other illicit drugs in the past. Kratom users were significantly more likely to use heroin, ecstasy, and ice with adjusted odds ratios of 39.7, 30.5, and 29.1, respectively. Of 195 who acknowledged kratom use in the past 12 months, 22 (11.3%) concurrently used other illicit drugs, including cannabis, amphetamine-type stimulants (ATSs), and inhalants. Polydrug use is common in Thai kratom users who are more likely to use opiates and ATSs in their lifetime. Another drug concurrently used was cannabis. Health personnel need to be aware of polydrug use in this population.